Civilizing the state : reclaiming politics for the common good - Restakis, John (New Society Publishers, 2021)
"Civilizing the State explores the disintegration of the liberal state in the face of rising polarization and corporate power. Drawing on international examples of democratic citizen-powered alternatives, it offers a vision of a partner state that could enable equity and economic democracy, driven by civil society."--